KONSEP PENDIDIKAN MULTIKULTURAL DALAM AL-QUR’AN SURAT AL-HUJURAT AYAT 12-13 - Restu Saputra; Nia Rahmanita Andria; Charles (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Research findings state that the review or intention of the Qur'an regarding multicultural education does not conflict with Islamic teachings in any way, especially the Qur'an as a source of Islamic law. The differences that exist in reality are an asset for scholars to study, as the Qur'an has explained. Through multicultural education, it is hoped that every person or group will accept and appreciate the differences between them, live with harmonious words in order to create peace and a prosperous nation. Another interesting finding in this research is that there are five roles of multicultural education in the view of the Koran; learn to live with differences, building three mutual aspects (trusting and understanding each other, open-mindedness, appreciation and interdependence), as there is no violent conflict resolution and peace. In fact, several characteristics are formed using Al-Qur'an verses and tafsir as references which show that the concept of multicultural education is parallel to Islamic teachings governing the structure of humanity living on earth, especially in the context of education.